2017
DOI: 10.1007/s00109-017-1528-2
|View full text |Cite
|
Sign up to set email alerts
|

Synovial cell production of IL-26 induces bone mineralization in spondyloarthritis

Abstract: IL-26 levels are higher in synovial fluid compared to plasma in spondyloarthritis. IL-26 was identified in axial facet joints of spondyloarthritis patients. Myofibroblasts from the spondyloarthritis synovium produce large amounts of IL-26. IL-26 induces bone mineralization in human osteoblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
4
23
2
Order By: Relevance
“…IL-26 has been also detected in the joints of patients suffering from rheumatoid arthritis (RA) (29) and spondyloarthritis (58). More precisely, IL-26 is expressed by fibroblast-like synoviocytes and, to a lower extent, by CD68 + macrophage-like synoviocytes present in inflamed joints from RA patients.…”
Section: The Il-26 Protein and Signaling Elementsmentioning
confidence: 99%
“…IL-26 has been also detected in the joints of patients suffering from rheumatoid arthritis (RA) (29) and spondyloarthritis (58). More precisely, IL-26 is expressed by fibroblast-like synoviocytes and, to a lower extent, by CD68 + macrophage-like synoviocytes present in inflamed joints from RA patients.…”
Section: The Il-26 Protein and Signaling Elementsmentioning
confidence: 99%
“…mineralization in joint tissue from patients with the chronic inflammatory disease spondyloarthritis (8).…”
mentioning
confidence: 99%
“…By contrast, SW982 cell migration rate was low when the cells were connected with BMSC, suggesting that BMSC might produce less chemokines than RAW264.7 cells did. Although synovial cells were implicated to have the ability to induce bone mineralization through production of IL-26 or miRNA, [ 29 ] in the co-culture of FLS, RAW264.7 and BMSC, the number of ALP staining-positive cells decreased, but the number of TRAP staining-positive cells increased. Our previous study showed that BMSC and RAW264.7 cell co-culture increased the activity of ALP, but did not affect TRAP activity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%